Pengaruh Bauran Pemasaran 7P Terhadap Keputusan Pembelian Pada Rumah Cantik Fazia Beauty - Sastya Putri; Denny Kurniawan; Suci Pawiati (Journal of Trends Economics and Accounting Research, 2023)
Mixed marketing is a tool tool used by marketers to get the desired response from the target market. Any marketing mix can have a positive or negative influence on consumer purchasing decisions. The study uses a descriptive survey approach, where the information collected from respondents uses a questionnaire. The object in this study is the consumer of the beautiful house Fazia Beauty located in JL. Brigjen Sutiyoso no. 32b City Metro Lampung. Data analysis such as validity, reliability, normality, linearity, homogenity, and double linear analysis is used. This study aims to find out whether product variables (X1), price (X2), place (X3), promotion (X4), people (X5), process (X6), physical evidence (X7) influence the purchase decision on the beautiful Fazia Beauty House in the Metro City. The number of samples selected allows researchers to collect data from respondents. Further, data from respondents were processed using the IBM SPSS Statistics Subscription program version 26. It is known that product variables (X1), price (X2), place (X3), promotion (X4), people (X5), process (X6), physical evidence (X7) simultaneously influenced the purchase decision. (Y).